LncRNA-42060 Regulates Tamoxifen Sensitivity and Tumor Development via Regulating the miR-204-5p/SOX4 Axis in Canine Mammary Gland Tumor Cells - Xu, Enshuang; Hu, Mengxin; Ge, Reidong; Tong, Danning; Fan, Yuying; Ren, Xiaoli; Liu, Yun (Frontiers in Veterinary Science, 2021)
Tamoxifen is the drug of choice for endocrine therapy of breast cancer. Its clinical use is limited by the development of drug resistance. There is increasing evidence that long non-coding RNAs (lncRNAs) are associated with tumor drug resistance. Therefore, we established two TAM-resistant cell lines, CHMpTAM and CHMmTAM. The different expression levels of lncRNA and miRNA in CHMmTAM and CHMm were screened by RNA sequencing, and the lncRNA-miRNA interactions were analyzed. LncRNA ENSCAFG42060 (lnc-42060) was found to be significantly upregulated in drug-resistant cells and tumor tissues. Further functional validation revealed that the knockdown of lnc-42060 inhibited proliferation, migration, clone formation, restoration of TAM sensitivity, and reduction of stem cell formation in drug-resistant cells, whereas overexpression of lnc-4206 showed opposite results. Bioinformatics and dual-luciferase reporter gene assays confirmed that lnc-42060 could act as a sponge for miR-204-5p, further regulating SOX4 expression activity and thus influencing tumor cell progression. In conclusion, we screened lncRNAs and miRNAs associated with TAM resistance in canine mammary gland tumor cells for the first time. lnc-42060 served as a novel marker that may be used as an important biomarker for future diagnosis and treatment.